A Comparison of Outcomes for Adults and Children Undergoing Resection for Inflammatory Bowel Disease: Is There a Difference?. (27th March 2014) - Mcmullin, Christine M.; Morton, Jonathan; Vickramarajah, Saranya; Cameron, Ewen; Parkes, Miles; Torrente, Franco; Heuschkel, Robert; Carroll, Nicholas; Davies, R. Justin
Abstract : Background . The incidence of inflammatory bowel disease (IBD) is increasing in the paediatric population. Since 2007, a single surgeon whose main practice is in the treatment of adults has performed surgery for IBD in adults and children within two dedicated multidisciplinary teams. Our aim was to assess and compare outcomes for adults and children following surgery for IBD. Methods . Analysis of a prospectively collected database was carried out to include all patients who had undergone resectional surgery for IBD between 2007 and 2012. Results . 48 adults and 30 children were included in the study. Median age for children was 14 years (range 8–16) and for adults was 33.5 years (range 17–64). Median BMI was 23 (range 18–38) and 19 (range 13–29.5) in adults and children, respectively (P < 0.001 ). Laparoscopic resection was performed in 27 (90%) children and 36 (75%) adults. Postoperative complication rates were comparable, 11 (23%) in adults versus 6 (20%) in children (P = 1.00 ). Conclusion . Resectional surgery for IBD in children has outcomes that compare favourably with the adult population, with the majority of cases being performed by a laparoscopic approach.